Allocation of investment costs for large-scale heat pumps supplying district heating. (August 2018) - Pieper, Henrik; Ommen, Torben; Buhler, Fabian; Paaske, Bjarke Lava; Elmegaard, Brian; Markussen, Wiebke Brix
Abstract: Large-scale heat pumps (HPs) are proposed as a technology to efficiently utilize intermittent wind power and other renewable sources. More than 25 large-scale HPs have been installed over the past decade to supply district heating (DH) in Denmark. A continuous increase is expected in the coming years. The HP projects differ in size, configuration, components and heat source. All these have an impact on the investment costs, which poses challenges for estimating costs, e.g. when planning new HP projects. For this paper, the investment costs of existing and planned electrically driven large-scale HPs were analyzed. All analyzed HPs use natural refrigerants and supply DH in Denmark. The total investment costs were divided into different categories to identify cost correlations for each of them depending on the heat source and HP capacity. The developed cost correlations were combined and verified by comparing the resulting correlations with the total investment costs of the considered HPs. Different intervals of the specific total investment costs for HPs depending on the heat source and HP capacity were derived. They identified the most and least expensive heat sources for HP capacities between 0.5 MW and 10 MW. It was shown that a considerable amount ( 50 %) of the investment costs was placed on other parts than the HP itself.